Performance and economic enhancement of a dewaxing casting process using a heat pump drying system - Win-Jet Luo; Amir Reza Ansari Dezfoli; Swami Nath Maurya; Bivas Panigrahi; Pei-Tang Wang (Case Studies in Thermal Engineering, 2025)
This study investigates integrating a heat pump drying system into the dewaxing and drying process of investment casting through numerical simulations and experimental validation. A mathematical model was developed to analyze drying performance by incorporating energy transfer, mass transport, evaporation, and moisture diffusion in porous media. The study examined temperature and airflow distribution within the drying chamber, optimizing the drying environment to ensure uniform conditions. Experimental results demonstrated that the heat pump drying system effectively reduced drying time from 38 h to 20.5 h, a 46 % reduction while maintaining a high product yield rate above 98 %. The system also achieved a 47.1 % reduction in energy consumption compared to conventional drying chambers, with a specific moisture extraction rate (SMER) of 0.945 kg/kWh, and the power cost per product reduced from USD 2.67 to USD 1.42. The key findings highlight that primary evaporation at the shell surface occurs rapidly, while secondary evaporation within the mold is diffusion-limited, affecting efficiency in thicker molds. The heat pump drying system enhances productivity and quality and contributes to sustainability by reducing operational costs and CO2 emissions. These results highlight the potential of heat pump technology as an energy-efficient and environmentally friendly alternative for industrial drying applications in investment casting.